Tuning the 2LMCT Deactivation of Cyclometalated Iron Carbene Complexes with Electronic Substituent Effects - Mishra, Abhishek; Sharma, Kumkum; Johnson, Catherine Ellen; Fosu, Emmanuel Adu; Schwarz, Jesper; Prakash, Om; Gupta, Arvind Kumar; Huang, Ping; Lindgren, Fredrik; Häggström, Lennart; Bendix, Jesper; Jakubikova, Elena; et al. (Chemistry - A European Journal, 2025)
FeIII complexes based on the [FeIII(ImP)2]+ motif (ImP = bis(2,6-bis(3-methylimidazol-2-ylidene-1-yl)phenylene)), where the ligand contains both carbene and cyclometalated moieties, are a promising class of photoactive materials made from this abundant metal. In this work, it is shown that bromo or furanyl substituents attached to the cyclometalating moiety of the ImP ligands stabilize the 2LMCT excited state to very different extent resulting in opposing effects on the 2LMCT lifetime. For [FeIII(ImPBr)2]+, the lifetime (255 ps) of its moderately stabilized 2LMCT state (1.85 eV) is slightly increased compared to the parent complex (1.90 eV, 240 ps) pointing to an increased barrier for deactivation via the 4MC state and enabling applications as photoredox catalyst. In contrast, the 2LMCT energy of [FeIII(ImPFur)2]+ is lowered substantially to a value of 1.63 eV due to the extended π-system of the ligands and the reduced energy gap favors internal conversion directly to the ground state resulting in a considerably reduced 2LMCT lifetime of 59 ps. These findings have general implications for design of ligand modifications aiming at extended LMCT lifetimes and/or modified ground and excited state potentials.
Publisher Copyright: © 2025 The Author(s). Chemistry – A European Journal published by Wiley-VCH GmbH.
Keywords: iron; N-heterocyclic carbene; photophysics; photoredox catalysis; Potential energy diagrams